Quality Analysis of Leaf and Stem Extracts of the Mikania micrantha - Makhabbah Jamilatun; Pradea Indah Lukito; Intan Kumalasari (Journal of Health Science and Medical Therapy, 2026)
Mikania micrantha (Sembung Rambat) is known in traditional medicine because it contains various bioactive compounds that have the potential as bioactive agents for pharmaceutical products and functional foods. The purpose of this study was to determine the quality of Mikania micrantha leaf and stem extracts obtained from Watualang Village, Ngawi. This study used an experimental research type, which included specific quality parameter tests, namely organoleptic tests and phytochemical screening, as well as non-specific quality parameter tests, namely water content and ash content. The results obtained, the yield of Mikania micrantha leaf and stem extracts were 14.32% and 13.12%, respectively. The specific quality parameters of Mikania micrantha extract, organoleptic test in the form of a thick green extract with a distinctive odor of the extract. Phytochemical screening, Mikania micrantha leaf and stem extracts contain phenol, flavonoid, steroid and sesquiterpene compounds. Non-specific quality parameters of Mikania micrantha extract include water content and ash content. The water content obtained in the leaf and stem extracts of Mikania micrantha were 9% and 8.45%, respectively. The ash content of the leaf and stem extracts of Mikania micrantha were 13.17% and 10.67%, respectively. The specific and non-specific quality parameters of the methanol extract of Mikania micrantha leaves and stems obtained from Watualang Village, Ngawi, have met the extract quality requirements.